Narrative Gaps and Moral Blindness: Stevens as an Unreliable Narrator in Ishiguro’s The Remains of the Day (International Journal of Food and Nutritional Sciences, 2022)
Using Ansgar Nünning’s theory of textual signals, this paper examines Stevens’ unreliable narration in Kazuo Ishiguro’s The Remains of the Day in order to examine the intricate relationship between memory, emotion, and identity.